The Role of the Habituation Method in Developing Children's Independent Behavior - Riswandi, Fitta Nurisma; Nisa, Muhibbatun; Sasmita, Wikan; Tiariyanti, Afifa (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2025)
Independence in early childhood serves as a fundamental pillar in character formation, yet this attribute is increasingly undermined by the rise of individualistic tendencies in the era of globalization. This study investigates the role of the habituation method in fostering independent behavior among young children at Kusuma Mulia Nambaan school. Employing a descriptive qualitative research design, data were gathered through direct observation, in-depth interviews with educators and caregivers, and the analysis of institutional documentation. Findings reveal that consistent implementation of habituation through routine activities, such as arranging footwear, returning toys, and completing assigned tasks without external assistance, significantly enhances children's self-reliance. These practices cultivated decision-making confidence and task completion autonomy in participants. The research underscores the critical role of structured habituation in promoting not only independence but also the broader development of social-emotional competencies. The study offers empirical support for integrating habituation-based strategies in early childhood education settings as a means of strengthening foundational character traits in an increasingly complex social landscape.